Heavy Metal Fe and Cr Content in The Water, Sediment and Tubifex sp. Living in The Sail River Pekanbaru - Retno Ningrum; Budijono Budijono; Hasbi Hasbi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract             Sail River has been polluted by heavy metals, especially Fe and Cr. Those heavy metals may accumulate in the body of aquatic organisms, including silk worm(Tubifex sp.). This research aims to understand the content of Fe and Cr in the water, sediment and silk worm (Tubifex sp.) obtained from the river. Sampling was done three times, once in two weeks, from December 2017 – January 2018. Sample of water, sediment and silk worm (Tubifex sp.) were taken from 3 stations, namely station I (in the upstream), station II (in the residential area) and station III (in the downstream). The sample was analyzed using AAS. Result shown that the content of Fe in the water were(0.531 – 0.871 mg/L), sediment were (25.10 – 39.88 mg/kg), and silk worm (Tubifex sp.) were (46.05 – 56.69 mg/kg)respectively. While the content of Cr in the waterwere(0.117 – 0.162 mg/L, sediment were (14.66 – 25.01 mg/kg) and silk worm(Tubifex sp.) were(4.65 – 9.17 mg/kg) respectively. It was concluded that the water, sediment and silk worms from the Sail River were already contaminated with Fe and Cr. Keyword : heavy metals, polluted river, silk worm, iron, chromium